Measurement of backscattering strength of artificial bubbles in the Southern Sea of the Korean Peninsula - Bae, Ho Seuk; Kim, Won-Ki (Frontiers in Marine Science, 2024)
Bubbles greatly affect the propagation of sound waves as the acoustic characteristics of a bubble cluster in water are distinct from those of undisturbed water. Therefore, bubble clusters affect the ability of sensors to detect underwater targets by blocking or reflecting sound waves. Additionally, the bubble wakes produced by ships in movement can be detected by wake-homing torpedoes, thus greatly threatening the safety of the ship. Thus, research on bubble dynamics in water is crucial for the development of military technology. Recently, we conducted a quantitative estimation of the acoustic characteristics of artificial bubbles, including their backscattering strength, existence time, population density spectrum level and void fraction in an ideal water-tank environment. Based on our previous findings, the present study sought to measure the acoustic characteristics of artificial bubbles using an acoustic Doppler current profiler (ADCP) in the southern sea of the Korean Peninsula, which is a real marine environment. Additionally, we validated the ADCP measurements by comparing them to those obtained using a scattering strength measurement system (SSMS) developed by our team. Collectively, our findings provide a basis for the development of military technology, as well as for the study of bubble in water.